Analysis and improvement of hot work management in China. Issue 1 (9th January 2023) - Wang, Xin
Abstract: Hot work, work involving electric or gas welding, cutting, brazing, or similar flame or spark‐producing operations, is a major industrial hazard. Many countries have formulated relevant regulations and standards for hot work to regulate their management procedures and operational requirements. This article compares and analyses the safety‐related regulations and standards for hot work in China and the United States. The article puts forward relevant suggestions for the revision and improvement of China's hot work regulations and standards in comparison with the US regulations and standards. In terms of details, the US regulations and standards are more scientific, stringent, and guiding. China's standards are more closely related to China's national conditions, but some provisions lack scientific basis and are poorly operable. Further enhancement of the scientific, guidance, and operationality of China's hot work‐related regulations and standards is recommended.